Smart Box Media Based on Differentiated Learning in Natural and Social Sciences Subjects for V Grade Student - Mardani, Ni Kadek Dwi Wahyu; Made Vina Arie Paramita (Universitas Pendidikan Ganesha, 2024)
The use of various media and learning methods greatly influences students' learning outcomes. This study aims to develop smart box media based on differentiated learning in the subject of Natural and Social Sciences with the material of my region my proud for fifth grade elementary school students. This type of research is included in development research by adapting the ADDIE model which goes through 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. This study involved design experts, content/material experts, design experts, and learning media experts, as well as 29 fifth grade elementary school students. The methods used in data collection were questionnaires and multiple-choice tests. The data analysis techniques used were quantitative descriptive analysis and inferential statistical analysis (t-test). The results of the study showed the feasibility based on the results of the expert assessment of design, content, design, media, individual trials, and small group trials in sequence, namely 93.18%, 96.67%, 92.5% 92.5%, 96.67%, and 91.67% which are included in the very good category. The effectiveness test with a one-sample t-test obtained tcount of 5.583, while the ttable value at a significance level of 5% with dk = 28 was 1.701. These results indicate that tcount > ttable or 5.583 > 1.701, so H0 is rejected and H1 is accepted. It can be concluded that smart box media based on differentiated learning is feasible and effective to be applied to the subject of science with the material of my proud region for grade V students.